Implementasi dan Pengaturan Hak Anak Dalam Hukum Indonesia - Sri Nurnaningsih Rachman; Andi Yusuf Katili (Jurnal Hukum Bisnis, 2023)
This research aims to understand the implementation and regulation of children's rights in Indonesian law. This research method is descriptive with a normative approach. Children are entrusted by God, the creator of the universe, where all elements are united in life that need and protect each other. The law regulates how to handle when a minor commits a criminal act, whether they must be tried according to the Criminal Code (KUHP) or mediation is carried out in accordance with applicable legal provisions. The results of the research show that minors who have already committed delinquency or criminal acts and have resulted in legal prosecution can receive guidance within their family environment. Or in other words, children are returned to their parents to be educated and trained so that they do not commit criminal acts in the future.